2020
DOI: 10.1088/1361-6528/ab898b
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced thermal properties for nanoencapsulated phase change materials with functionalized graphene oxide (FGO) modified PMMA

Abstract: A novel kind of nanoencapsulated phase change materials containing n-octadecane and n-butyl stearate as binary cores and functionalized graphene oxide modified poly(methyl methacrylate) as hybrid shells (FGO/PMMA-NanoPCMs) with superior thermal storage capability was successfully prepared by surfactant-free emulsion polymerization with reactive emulsifiers. The morphology, structure and thermal stability of graphene oxide (GO) and functionalized graphene oxide (FGO) were characterized by SEM, FT-IR, XRD and TG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…However, due to the inherently low thermal conductivity of PCM, it is a challenge to achieve efficient heat dissipation in temperature management, which limits their further engineering applications [ 17 , 18 ]. To address this drawback, various methods have been developed to improve the thermal conductivity of PCM, including inserting metal fins [ 19 , 20 ], adding high thermal conductivity nanoparticles [ 21 ], embedding metal foams [ 22 , 23 ] and microencapsulating [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the inherently low thermal conductivity of PCM, it is a challenge to achieve efficient heat dissipation in temperature management, which limits their further engineering applications [ 17 , 18 ]. To address this drawback, various methods have been developed to improve the thermal conductivity of PCM, including inserting metal fins [ 19 , 20 ], adding high thermal conductivity nanoparticles [ 21 ], embedding metal foams [ 22 , 23 ] and microencapsulating [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The dispersion of GO in PEG is closely related to its degree of oxidation [ 14 ]. It was found that the modification of GO using surface modifiers resulted in better binding to PEG and improved its dispersion properties as well as its crystal structure [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The multilayer microcapsules not only had a thermal energy storage property, but also possessed UV-shielding functions. Zhou et al [29] used functionalized graphene oxide (FGO) as a Pickering emulsifier to prepare phase-change nano-capsules with PMMA/FGO hybrid shells via surfactant-free emulsion polymerization. The results indicated that the latent enthalpy, thermal conductivity and thermal stability of the nano-capsules were effectively improved in the PMMA-NanoPCMs modified with FGO.…”
Section: Introductionmentioning
confidence: 99%